Social support in old age: differences by sex in a sample from northern Mexico - Rosa Isabel Garza-Sánchez; José González-Tovar (Interacciones)
Social support is perceived as information from the environment that allows a person to feel loved, esteemed and sustained. The objective of this study was to compare whether there are significant differences between men and women in the level of social support perceived by the family, friends and other meaningful support networks. A quantitative cross-type study was carried out. We used the multi-dimensional scale of perceived Social support (MSPSS), measures the perceptions of support of three main sources: family, friend and other significant, obtained an ordinal alpha coefficient of ω =. 934. We used an intentional sampling, participated 396 adults (Mage = 69.81, of = 6.95), 56.3% were women and 43.8% men. Significant differences were found in the three dimensions of social support in the older adult, with a smaller effect size than a standard deviation. Older women have a better perception of social support that contributes to their well-being. The role that people around the older adult play is meaningful to him and the quality of the existing relationship is more important, the family becomes that close support network where the older adult feels protected and loved.